Stakeholders' perspectives on training over the counter medicine sellers and Community-based Health Planning and Services facilities to dispense antibiotics in Ghana - Samuel Afari-Asiedu; Marlies Hulscher; Martha Ali Abdulai; Ellen Boamah-Kaali; Heiman F. L. Wertheim; Kwaku Poku Asante (Taylor & Francis Group, 2021)
Background Dispensing of antibiotics by over the counter medicine sellers (OTCMS) is a major driver of inappropriate use and resistance in low and middle income countries. Recent studies in Ghana revealed the need to consider training OTCMS and Community-based Health Planning and Services (CHPS)/health posts to dispense some antibiotics. Feasibility of training OTCMS and CHPS to dispense some antibiotics was explored in this study. Methods This was an explorative study involving 10 in-depth interviews (IDIs) among staff of Ghana health services (GHS), pharmacy council and the association of OTCMS at the district and regional levels. Next, findings were presented to the Ghana Antimicrobial Resistance (AMR) platform for further discussions at the national level. Five IDIs were also performed among selected members of the AMR platform as a follow-up on emerging issues. Data were thematically analysed and presented as narratives with quotes to support the findings. Results Two opposing views were found in our study. Leadership of OTCMS and GHS staff at the district health directorate supported the suggestion that OTCMS and CHPS should be trained to dispense specific antibiotics because they are already dispensing them. The leadership of OTCMS explained that some of their members are experienced and could be trained to improve their practices. In contrast, participants from pharmacy council, GHS in the region and national AMR platform generally alluded that OTCMS and CHPS should not be trained to dispense antibiotics because their level of education is inadequate. GHS personnel from the region further explained that training OTCMS could further compromise inappropriate antibiotic use in the context of already weak regulation enforcement. GHS and pharmacy council in the region rather suggested that OTCMS and CHPS should focus on public health education on disease prevention and appropriate antibiotic use. Conclusions There is general lack of consensus among stakeholders on whether OTCMS and CHPS should be trained to dispense specific antibiotics. Further stakeholder engagement is required to carefully consider this suggestion as views on feasibility differ. Ministries of health and healthcare agencies in Ghana and LMIC should improve access to approved health services to improve antibiotic use in rural settings.